Managing Organizational Structure for University Advancement: An Assessment at Asia-Pacific International University - Keough, Ryan; Kazimoto, Paluku (11th International Scholars Conference, 2018)
Organizational structures are important factors because they help organizations ensure that they are designed to accomplish their institutional mission and vision. The aim of this study was to look at organizational structures and how they affect university advancement. The study used a correlational design for analysis, and convenience sample technique was used for respondents selection (n = 34). Findings indicated that a flat, matrix and organic organizational structures were the better suited structures for university advancement. There were statistically significant relationships between University Advancement’s marketing factor and the matrix organizational structure (r =.461, p = 0.006); marketing and the flat organizational structure (r=.385, p = 0.025); the fundraising university advancement and the matrix organizational structure (r =.410, p=.016); alumni with the matrix organizational structure (r =.400, p =.019) and with organic organizational structure (r =.438, p =.010). It was concluded that organizational structures have significant positive influence on university advancement. Recommendations include further studies to include more institutions, increased institutional focus on university advancement and its functions, and instituting a collaborative environment with a flat, organic or matrixed organizational structure.